Te Tiriti o Waitangi/Treaty of Waitangi 1840: its influence on health practice - Wilson, Denise; Haretuku, Riripeti (Cultural safety in Aotearoa New Zealand, 2015)
In this second edition of Cultural Safety in Aotearoa New Zealand, editor Dianne Wepa presents a range of theoretical and practice-based perspectives adopted by experienced educators who are active in cultural safety education. Dianne Wepa, Hawkes Bay District Health Board, NZ.
Keywords: bicultural; health; tiriti o waitangi/treaty of waitangi; treaty principles

Chapter 2: Te Tiriti o Waitangi: A Blueprint for the Future - Campbell, Bronwyn (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: tiriti o waitangi/treaty of waitangi; treaty principles

Chapter 15: From the Sideline: Tikanga, Treaty Values and Te Papa - Tapsell, Paul (Waitangi Revisited, 2005)
Keywords: bicultural; government relations; history; land tenure; mana whenua; marae; museums; race relations; te papa museum; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty principles

Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting